Exploring the Potential of Sucralose as a Cryopreservative for Red Blood Cells - Holloman, Matthew (East Carolina University, 2017)
Cryopreservation is a technique that involves freezing living cells to preserve them in long-term storage. Freezing and preserving living cells would not be possible without the assistance of cryopreservatives. Many cryopreservatives like DMSO and glycerol are currently used to protect living cells as they freeze. However, because of potential toxicity and the need for washing steps in blood transfusion medicine, there is need for alternative cryopreservatives that are both effective and safe for living cells. In this paper, sucralose, an artificial sweetener, is tested as a cryopreservative at varying concentrations. In addition, sucralose was paired with a traditional cryopreservative, DMSO, to observe if its efficacy was altered. The study showed that sucralose does offer cryoprotective ability, and its protection increases as the concentration increases. Pairing cryopreservatives was shown to be less effective. Presented data could be useful in further study of cryopreservation and transfusion medicine.
Keywords: sucralose; cryopreservation; hemolysis